2017
DOI: 10.1177/0042098017698416
|View full text |Cite
|
Sign up to set email alerts
|

Home of last resort: Urban land conflict and the Nubians in Kibera, Kenya

Abstract: Amid expansive and often informal urban growth, conflict over land has become a severe source of instability in many cities. In slum areas, policies intended to alleviate tensions, including upgrading programs, the legal regulation of informal tenure arrangements, and the reform of local governance structures, have had the unintended consequence of also spurring violence and conflict. This paper analyzes the conflict over a proposed 'ethnic homeland' for the Nubian community in the Kibera slum in Nairobi, Keny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Underneath the formal ownership of the land by the national government in informal settlements, often local and national politicians are the major owners of buildings as ‘slumlords’, making them an arena for political mobilisation around election time. This has been particularly important in the rising of Raila Odinga, leader of the opposition, who has mobilised Kibera (where Sanergy work) as one of his key strongholds (Elfversson & Höglund, 2018). This can often lead to expanding populations and voters of tribal groups being moved into informal settlements in the run‐up to elections.…”
Section: Revealing the Complex Fragmentation Of Sanitation Governancementioning
confidence: 99%
“…Underneath the formal ownership of the land by the national government in informal settlements, often local and national politicians are the major owners of buildings as ‘slumlords’, making them an arena for political mobilisation around election time. This has been particularly important in the rising of Raila Odinga, leader of the opposition, who has mobilised Kibera (where Sanergy work) as one of his key strongholds (Elfversson & Höglund, 2018). This can often lead to expanding populations and voters of tribal groups being moved into informal settlements in the run‐up to elections.…”
Section: Revealing the Complex Fragmentation Of Sanitation Governancementioning
confidence: 99%
“…The fundamental difference between the applications of CBA in this research and previous studies lies in determining the cost and benefit components associated with the interests of diverse stakeholders. As previous studies suggested, mapping and assessing various stakeholders are essential in studying urban development conflicts and evaluations (Elfversson and Höglund, 2018;Lombard and Rakodi, 2016;Nae, Dumitrache et al, 2019;Yuan, Chen et al, 2018;Zepharovich, Ceddia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The change of administration in the Kibera area in the beginning of 1928 from a military to civil society was lacking local authority to administer the area, which led to an administrative grey area where tax was not collected. This opened the area up to the indigenous tribes of Kenya who intensively moved into Nairobi in search of work [45]. Given the difficulties in resettling the Nubian population in Kibera, the government stopped distributing residence permits to family members of the war veterans and neglected the steady supply of water and sewerage to force the residents to resettle elsewhere, with an intention of eventually dismantling Kibera as a housing site and opening the area for the expansion of Nairobi City [6,44].…”
Section: Discussing Differences In Livelihood Welfare Factors Across ...mentioning
confidence: 99%